2008
DOI: 10.1530/rep-07-0479
|View full text |Cite
|
Sign up to set email alerts
|

Generation of multipotent cell lines from a distinct population of male germ line stem cells

Abstract: Spermatogonial stem cells (SSCs) maintain spermatogenesis by self-renewal and generation of spermatogonia committed to differentiation. Under certain in vitro conditions, SSCs from both neonatal and adult mouse testis can reportedly generate multipotent germ cell (mGC) lines that have characteristics and differentiation potential similar to embryonic stem (ES) cells. However, mGCs generated in different laboratories showed different germ cell characteristics, i.e., some retain their SSC properties and some hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 30 publications
(34 reference statements)
3
78
0
Order By: Relevance
“…1d) (Takehashi et al 2007b). The pluripotency of SSCs was subsequently confirmed by several other groups (Guan et al 2006;Seandel et al 2007;Izadyar et al 2008;Ogawa 2008). However, there are pronounced differences in the phenotypic and functional characteristics of these ES-like cells, which will be the focus of future studies.…”
Section: The Development Of a Long-term Culture System: Germ-line Stementioning
confidence: 78%
“…1d) (Takehashi et al 2007b). The pluripotency of SSCs was subsequently confirmed by several other groups (Guan et al 2006;Seandel et al 2007;Izadyar et al 2008;Ogawa 2008). However, there are pronounced differences in the phenotypic and functional characteristics of these ES-like cells, which will be the focus of future studies.…”
Section: The Development Of a Long-term Culture System: Germ-line Stementioning
confidence: 78%
“…However, the iconoclastic finding of Kanatsu-Shinohara et al (Kanatsu-Shinohara et al 2004) demonstrated that neonatal murine SSCs produced ESC-like cells when isolated from the testis and grown for extended periods in ESC culture conditions. Although initial work was done with neonatal SSCs (Kanatsu-Shinohara et al 2004;Simon et al 2009), subsequent work showed that adult murine SSCs (Glaser et al 2008;Izadyar et al 2008;Seandel et al 2007;Guan et al 2006) grown for 4-7 weeks in vitro also produced a low frequency of ESC-like colonies. These ESC-like cells can give rise to cell types derived from all three embryonic germ layers, and also produce teratomas when injected subcutaneously into nude mice.…”
Section: Spermatogonial Stem Cells Are Pluripotentmentioning
confidence: 99%
“…Izadyar et al (2008) suggested that the Oct4 + /c-Kit + subset of mouse GSCs in the in vitro culture generated a distinct cell population whose properties are very similar to those of pluripotent stem cells.…”
Section: Factors Affecting Reprogramming Efficiencymentioning
confidence: 99%